The implementation of sandwich graphic organizer in teaching writing to the tenth grade students of SMAN 1 Jiwan - Puput Karunia Dewi; S Sumani; Brigitta Septarini (English Teaching Journal : A Journal of English Literature, Language and Education, 2018)
This research is conducted to explain the implementation, the problems, and the solutions of problems in the Implementation of Sandwich Graphic Organizer in Teaching Writing to the Tenth Grade Students of SMAN 1 Jiwan in the schooling year of 2016/2017. This research uses descriptive qualitative research. The participants of the research are the English teacher and students of X-A class of SMAN 1 Jiwan. The research uses purposive sampling technique. The techniques which are used to collect the data are observation, interview, and documentation. While, the techniques of the data analysis are: data condensation, data display, and conclusion and verification. The results of this research are the teacher prepares syllabus, RPP, and the papers of picture Sandwich Graphic Organizer. The steps are pre-activities, whilst-activities, and post-activities. Otherwise, some students get difficulties in managing their time, some students make mistakes in using V2 that is used in writing recount text, some students get difficulties in expressing their ideas from Indonesian to the English language because of minimum of vocabulary, and some students forget to write a capital letter in the beginning of the sentence and full stop in the ending of the sentence. Then, the solutions of problems in the implementation Sandwich Graphic Organizer are: the teacher explains again about the steps of using technique Sandwich Graphic Organizer, the teacher divides the time of the students when the students should write the outline and when the students should develop their outline, the teacher gives the command for the students to open their dictionary to check the list of verb 2, the teacher asks the students to open their dictionaries when they are difficult in translating their ideas, and the teacher asks the students to pay attention to the punctuation when writing.This research is conducted to explain the implementation, the problems, and the solutions of problems in the Implementation of Sandwich Graphic Organizer in Teaching Writing to the Tenth Grade Students of SMAN 1 Jiwan in the schooling year of 2016/2017. This research uses descriptive qualitative research. The participants of the research are the English teacher and students of X-A class of SMAN 1 Jiwan. The research uses purposive sampling technique. The techniques which are used to collect the data are observation, interview, and documentation. While, the techniques of the data analysis are: data condensation, data display, and conclusion and verification. The results of this research are the teacher prepares syllabus, RPP, and the papers of picture Sandwich Graphic Organizer. The steps are pre-activities, whilst-activities, and post-activities. Otherwise, some students get difficulties in managing their time, some students make mistakes in using V2 that is used in writing recount text, some students get difficulties in expressing their ideas from Indonesian to the English language because of minimum of vocabulary, and some students forget to write a capital letter in the beginning of the sentence and full stop in the ending of the sentence. Then, the solutions of problems in the implementation Sandwich Graphic Organizer are: the teacher explains again about the steps of using technique Sandwich Graphic Organizer, the teacher divides the time of the students when the students should write the outline and when the students should develop their outline, the teacher gives the command for the students to open their dictionary to check the list of verb 2, the teacher asks the students to open their dictionaries when they are difficult in translating their ideas, and the teacher asks the students to pay attention to the punctuation when writing.